Meta Analysis of Factors Affecting the Birth of Infants with Labiopalatoschizis - Nining Sunarti; Tri Mochartini (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Labiospalatoskizis is caused by failure in the process of joining the lips while still in the fetus. This disorder can cause many disorders such as disorders such as eating disorders, speech disorders, ear irritation, and dental and oral disorders. Many factors can cause this disorder, namely exposure to cigarette smoke and metal exposure during pregnancy. The purpose of this meta-analysis was to analyze the effect of cigarette smoke exposure and metal exposure on labiospalatoskizis events. This study was conducted by systematic review and meta-analysis. Research data is sought from several indexing including: PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords "smoking AND Orofacial Clefts", "heavy metal AND labiospalatoschizis", "smoke AND metal exposure AND cleft lift AND adjusted odds ratio", and "factors AND labiospalatoskizis AND adjusted odds ratio". There were 6 articles with 2 analysis results, namely: heavy metal exposure (OR: 3.18; 95% CI: 2.45 – 4.12; p value <0.001) and secondhand smoke exposure (OR: 5.40; 95% CI: 4.26 – 6.86; p value <0.001).